Obesity, insulin resistance, adipocytokines and breast cancer: New biomarkers and attractive therapeutic targets. - Dalamaga, Maria (World J Exp Med, 2013)
Worldwide, breast cancer (BC) represents the most common type of non-skin human malignancy and the second leading cause of cancer-related deaths amid women in Western countries. Obesity and its metabolic complications have rapidly become major global health issues and are associated with increased risk for cancer, especially BC in postmenopausal women. Adipose tissue is considered as a genuine endocrine organ secreting a variety of bioactive adipokines, such as leptin, adiponectin, resistin and nicotinamide phosphoribosyl-transferase/visfatin. Recent evidence has indicated that the constellation of obesity, insulin resistance and adipokines is associated with the risk and prognosis of postmenopausal BC. Direct evidence is growing rapidly supporting the stimulating and/or inhibiting role of adipokines in the process of development and progression of BC. Adipokines could exert their effects on the normal and neoplastic mammary tissue by endocrine, paracrine and autocrine mechanisms. Recent studies support a role of adipokines as novel risk factors and potential diagnostic and prognostic biomarkers in BC. This editorial aims at providing important insights into the potential pathophysiological mechanisms linking adipokines to the etiopathogenesis of BC in the context of a dysfunctional adipose tissue and insulin resistance in obesity. A better understanding of these mechanisms may be important for the development of attractive preventive and therapeutic strategies against obesity-related breast malignancy.